The Members of the Highly Diverse Crassostrea gigas Integrin Family Cooperate for the Generation of Various Immune Responses - Lv, Zhao; Qiu, Limei; Wang, Weilin; Liu, Zhaoqun; Liu, Qing; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2020)
Studies on invertebrate immune receptors can provide insights into characteristics specific to innate immune system. Here, eight α and three β integrins are identified from an invertebrate, the Pacific oyster Crassostrea gigas, and their possible immune functions are studied. Oyster α/β integrins exhibit a higher degree of sequence and structural variability than the members from Homo sapiens and Drosophila melanogaster. The analysis reveals that oyster RGD- and laminin-binding receptor homologs are present in the phylogenetic tree of α integrins, but the other six oyster α integrins mainly form a species-specific branch; meanwhile, oyster β integrins are clustered with insect β integrins but distinct from a member from the mollusk Biomphalaria glabrata. Although phylogenetically lacking the important α integrin branches of LDV-binding, PS3-type, and αI-containing integrins, oyster integrins can bind to most ECM ligands, including RGDCP, LDVCP, GFOGERCP, and laminin protein in a distinct binding pattern. Besides, oyster integrins are distributed in different hemocyte subpopulations, while only specific integrins are selectively involved in hemocyte phagocytosis, migration, and encapsulation, and some of them participate in more than one immune response in a sophisticated pattern. Especially, oyster β integrins are arranged in the core to mediate complex immune responses, unlike the counterparts in humans that mainly depend on αI-containing integrins to incite immune reactions. This study represents the first comprehensive attempt to reveal the structural and evolutionary features of the integrin family and their involvement in cellular immune responses in the non-model invertebrate C. gigas and sheds light on the characteristics specific to the innate immune system in the integrin family.